Sensitivitas Konsumen : Studi Tentang Persepsi Mahasiswa Pada Aksi Sosial Perusahaan Yang Mempengaruhi Pembelian Di Shopee - Wulandari, Tiara; Fadli Hidayah, Faida; Hestiani; Dwi Lestari, Ita; Nuramadani, Afi; Tri Nugraha , Joko (Faculty of Social and Political Science, 2025)
This study aims to analyze and understand the level of consumer sensitivity, particularly among university students, towards corporate social responsibility, which influences their shopping choices on the e-commerce platform Shopee. In today's modern era, consumers in online shopping consider not only product price and quality, but also the moral and ethical values ​​​​embraced by the seller. This study used a descriptive quantitative method. The research sample consisted of 72 respondents, namely Public Administration students of Tidar University class of 2024, determined by the Slovin formula. Primary data were obtained through a closed questionnaire using a Likert scale, focusing on indicators of consumer sensitivity, corporate social responsibility, and purchasing decisions. The research findings revealed that student sensitivity to corporate social responsibility is very high. Most respondents are willing to pay more for products from sellers who implement good environmental practices, ensure gender equity for female employees, and contribute to job creation. Students also showed significant rejection of unethical businesses, with the percentage of agreeing/strongly agreeing reaching 86.2% to avoid stores with bad reputations and 73.6% to boycott sellers who are not socially responsible. The conclusion of this study confirms that social responsibility and ethics in business have become the main factors, more important than price and quality, in influencing student loyalty and purchasing decisions on Shopee e-commerce.